Microstructural characterization of ITZ in blended cement concretes and its relation to transport properties. (January 2016) - Wu, Kai; Shi, Huisheng; Xu, Linglin; Ye, Guang; De Schutter, Geert
Abstract: The improvements in the overall performances of concrete with blended materials were often ascribed to the modification of its hardened paste in general. In this paper, the effects of limestone filler (LF) and slag (GGBS) on chloride migration and water absorption of concretes with systematically varied aggregate properties were evaluated from the view point of ITZ by using BSE image, EDS, and MIP analysis. It was found that the incorporation of moderate amount of LF and GGBS would compact the microstructure of both ITZ and bulk cement matrix. The reduction in the pore volume (> 100 nm) contributes to the largest decrease in total porosity. Additionally, incorporating GGBS avoids the build-up of Ca(OH)2 within ITZ and provides a more uniform microstructure. The mechanism for the improvement in limiting water and ions penetration was found to be mainly related to the densification of bulk cement matrix rather than the modification of ITZ.